Multiobject optimization for scheduling in grid computing systems - Giang, Trịnh Thị Thúy; Vĩnh, Lê Trọng; Thành, Hoàng Chí; Thủy, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2012)
See full text